Cerebral changes and cerebrospinal fluid β-amyloid in Alzheimer's disease: a study with quantitative magnetic resonance imaging - Schröder, Johannes; Pantel, Johannes; Ida, N.; Essig, Marco; Hartmann, Tobias; Knopp, Michael V.; Schad, Lothar R.; Sandbrink, Rupert; Sauer, H.; Masters, C. L.; Beyreuther, Konrad (Molecular psychiatry, 1997)
Pathological and biochemical studies indicate that β-amyloid (βA4) deposition is a hallmark in the pathogenesis of Alzheimer's disease (AD).1-4 Neuroimaging studies demonstrate that the respective cerebral changes primarily strike the temporal lobe and the amygdala-hippocampus complex and may be reliably assessed using quantitative magnetic resonance imaging (MRI).5,6 Therefore one may expect that reduced βA4-levels are significantly correlated with measures of the temporal lobe rather than global cerebral atrophy in AD patients. To test this hypothesis in a clinical study, cerebrospinal fluid concentrations of total β A4 and its major C-terminal variations β A4 1-40 and β A4 1-42 were compared with cerebral changes as assessed by quantitative magnetic resonance imaging (MRI). Significantly (P < 0.05) reduced β A4 1-40 and β A4 1-42 levels were found in the AD patients (17 female; six male; AD/NINCDS-ADRDA-criteria)7 in comparison to the patients with major depression (seven female; two male; DSM-III-R).8 Within the AD group, βA4 and β xA4 1-42 levels were significantly correlated with the volume of the temporal lobes (r = 0.46 and r = 0.48, respectively) but none of the other volumetric measures. These findings indicate that changes in cerebral β A4 levels contribute to temporal lobe atrophy in AD and support the possibility that βA4 is central to the etiology of AD.
Gesehen am 16.11.2021